Gene Expression Analysis of the Endocannabinoid System in Presymptomatic APP/PS1 Mice - Vidal-Palencia, Laura; Ramon-Duaso, Carla; González-Parra, Jose Antonio; Busquets-Garcia, Arnau (Frontiers in Pharmacology, 2022)
Alzheimer’s disease (AD) is the most common type of dementia and neurodegeneration. The actual cause of AD progression is still unknown, the reason why no curative treatment is available. Recently, findings in human samples and animal models pointed to the endocannabinoid system (ECS) as a promising therapeutic approach against AD. However, the specific mechanisms by which cannabinoid drugs induce potential beneficial effects are still undefined. For this reason, it is required a full characterization of the ECS at different time points of AD progression considering important factors such as sex or the analysis of different brain regions to improve future cannabinoid-dependent therapies in AD. Thus, the main aim of the present study is to expand our knowledge of the status of the ECS in a presymptomatic period (3 months of age) using the AD mouse model APP/PS1 mice. First, we evaluated different behavioral domains including anxiety, cognitive functions, and social interactions in male and female APP/PS1 mice at 4 months of age. Although a mild working memory impairment was observed in male APP/PS1 mice, in most of the behaviors assessed we found no differences between genotypes. At 3 months of age, we performed a characterization of the ECS in different brain regions of the APP/PS1 mice considering the sex variable. We assessed the expression of the ECS components by quantitative Real-Time Polymerase Chain Reaction in the hippocampus, prefrontal cortex, hypothalamus, olfactory bulb, and cerebellum. Interestingly, gene expression levels of the type-1 and type-2 cannabinoid receptors and the anabolic and catabolic enzymes, differed depending on the brain region and the sex analyzed. For example, CB1R expression levels decreased in both hippocampus and prefrontal cortex of male APP/PS1 mice but increased in female mice. In contrast, CB2R expression was decreased in females, whereas males tended to have higher levels. Overall, our data indicated that the ECS is already altered in APP/PS1 mice at the presymptomatic stage, suggesting that it could be an early event contributing to the pathophysiology of AD or being a potential predictive biomarker.